Ethics of learners in educational institutions from the perspective of Indonesian law (Darul Arqam Nur-Ichsan School Sorong) - Suparto, Suparto; Hadi Tuasikal; Dwi Pratiwi Markus (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Education is synonymous with schools (formal institutions), while non-formal institutions are still neglected as one of the sub-systems in the world of education. Meanwhile, one of the non-formal institutions PKBM Darul Arqam Nur-Ichsan School Sorong is a non-formal educational institution that intensely cultivates religious character values. This research aims to describe the cultivation of religious character education values in students by PKBM Darul Arqam Nur-Ichsan School Sorong This research uses a qualitative approach with a case study research type. The selection of informants was done by purposive sampling. The data obtained was analysed using the Miles and Huberman Interactive Analysis Model with steps namely reducing data, displaying data and drawing conclusions. The results of the study describe the model of cultivating religious character values at PKBM Darul Arqam Nur-Ichsan School Sorong, namely the existence of AIK (Al-Islam Kemuhammadiyahan) subjects that provide Muslim personality development, and leaders, teachers and staff become role models / role models at PKBM Darul Arqam Nur-Ichsan School Sorong and the norms and values of PKBM Darul Arqam Nur-Ichsan School Sorong institutions make all PKBM Darul Arqam Nur-Ichsan School Sorong residents strive to carry out God's commands and stay away from His prohibitions. The implications of this research can be utilised for education offices and related educational institutions regarding character cultivation models in non-formal institutions.